Sublingual immunotherapy to house dust mite as an immunological intervention in refractory atopic dermatitis - Rasool, Roohi; Qadri, Qurteeba; Qureshi, Taha; Gull, Ayaz; Shafi, Tabasum; Shah, Zafar A (Indian Journal of Case Reports, 2019)
Sublingual immunotherapy (SLIT) with house dust mite (HDM) preparation has been shown to reduce disease severity in patientswith atopic dermatitis (AD). A 5-year-old girl with severe Atopic Dermatitis refractive to all possible pharmacotherapy was put onSLIT for dust mite and followed up for a period of one year. SLIT to dust mite proved highly effective in reducing the disease severityscore as well as prevention of exacerbations in this patient.